Knowledge on Alzheimer's Disease among Public Hospitals and Health Clinics Pharmacists in the State of Selangor, Malaysia - Mat Nuri, Thimarul Huda; Hong, Yet Hoi; Ming, Long Chiau; Mohd Joffry, Suhaidah; Othman, Muhamad Faiz; Neoh, Chin Fen (Frontiers in Pharmacology, 2017)
The prevalence of Alzheimer’s disease (AD) has increased with the fast growing of aging population, posing great challenges to provision of care for AD patients. Pharmacists play a vital role in the management of AD; this includes recognising early symptoms of AD, providing medication counselling to AD patients and their caretakers, and identifying potential adverse drug reactions. A comprehensive understanding of the disease progression, as well as the pharmacological therapy, is essential to provide effective care to AD patients. The level of knowledge about AD among the pharmacists, however, remains unknown. Hence, this study aimed to assess the knowledge on AD among the pharmacists in public hospitals and health clinics and its correlates. A clear picture of the characteristics associated with different levels of knowledge could facilitate the targeted re-training of pharmacists. The 30-item validated Alzheimer disease knowledge scale (ADKS) tool was pilot-tested and used in this cross sectional study. All pharmacists, from nine public hospitals and seven public health clinics in the State of Selangor, Malaysia were invited to participate in this cross-sectional survey. The ADKS score was computed and compared across demographics characteristics. A total of 445 pharmacists responded to the survey. These pharmacists had a moderate overall score in ADKS; nevertheless, high scores were recorded in the domains of treatment management and care giving. No difference in AD knowledge between pharmacists worked in public hospitals and health clinics, except for the domain of care giving (p = 0.033). Ethnicity and age group were independent predictors of ADKS score in the current study. The pharmacists in the current study had moderate AD knowledge. On-going education and training programme on AD, in particular the domains other than treatment management and care giving, should be provided to the pharmacists to ensure delivery of quality care to AD patients.